PWE-178 Impact Of Chronic Constipation On Healthcare Resource Use In The Uk: An Analysis Based On Electronic Medical Records. (9th June 2014) - Radford, M; Bloomfield, E; Joseph, A
Abstract : Introduction: Chronic constipation is a common condition with a substantial impact on health-related quality of life. The aim of this study was to assess healthcare resource use and prescription laxative costs associated with chronic constipation in the UK, using electronic medical records. Methods: The IMS Disease Analyzer database contains electronic medical records from primary healthcare practices in England and Wales. Patients were identified as having chronic constipation if they had: ≥2 international classification of diseases-revision 10 (ICD-10) codes for constipation within 12 months; or 1 primary constipation diagnosis and ≥2 laxative prescriptions in the 6 months before or 12 months after the constipation diagnosis. Patients with a diagnosis of irritable bowel syndrome or a record of opioid use were excluded. Records were analysed from 1 January 2008 to 31 December 2011 for the 12-month period following the first constipation diagnosis. Mortality, frequency of comorbidities, number of healthcare consultations, and total laxative prescriptions and costs were recorded and stratified by sex and age group (age 18–49, 50–64, 65–74, and ≥75 years). For patients with less than 12 months follow-up, data on costs, healthcare contacts and prescriptions were adjusted to an annual rate using a simple linear projection. Regression analyses were performed on a case basis to estimate the impact of covariates on laxative costs. Results: Overall, 10 371 patients with chronic constipation were identified, of whom 63% were women and 53% were ≥75 years old. Mortality during the 12-month follow up period was 8.4%. The most common co-morbidities were primary hypertension (32%) and type 2 diabetes mellitus (13%). Patients had a mean of 27.7 consultations (standard deviation [SD] 24.0), including 4.0 (SD 9.8) for constipation-related care, in the 12-month follow up period. In total, 92% of patients were prescribed laxatives; patients had on average 8.3 (SD 14.0) laxative prescriptions in the 12 month follow up, which using an average prescription cost of £4.28 resulted in a mean cost to the National Health Service of £35.41/person/year in 2011 GBP. An increase in prescription laxative cost was significantly associated with increasing age group, the presence of Parkinson's disease (proportional cost increase [PCI] 1.29, p < 0.0005), type 2 diabetes mellitus (PCI 1.08, p < 0.025) and multiple sclerosis (PCI 1.51, p < 0.0005). Conclusion: In this analysis of UK electronic medical records using the IMS UK Disease Analyzer database, the majority of patients with chronic constipation were elderly, and over 90% were prescribed laxatives. Higher treatment costs were associated with increased age and co-morbidity. Disclosure of Interest: M. Radford Employee of: IMS Health, which received funding from Shire to carry out this research., E. Bloomfield Employee of: IMS Health, which received funding from Shire to carry out this research., A. Joseph Employee of: Shire.